2001
DOI: 10.1128/jvi.75.3.1195-1204.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Serum Immunoglobin Contributes to Protection from Herpes Simplex Virus Type 2 Genital Infection in the Presence of Immune T Cells

Abstract: Herpes simplex type virus 2 (HSV-2) is a sexually transmitted pathogen that causes genital lesions and spreads to the nervous system to establish acute and latent infections. Systemic but not mucosal cellular and humoral immune responses are elicited by immunization of mice with a replication-defective mutant of HSV-2, yet the mice are protected against disease caused by subsequent challenge of the genital mucosa with virulent HSV-2. In this study, we investigated the role of immune serum antibody generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 55 publications
6
49
0
2
Order By: Relevance
“…However, as discussed above, transfer of the induced gC antibodies alone was not sufficient for solid protection, and, therefore, the presence of immune T cells seems to be required for full protective capacity of immune serum antibodies, as also reported for herpes simplex virus type 2 (HSV-2) infection (36).…”
Section: Discussionmentioning
confidence: 81%
“…However, as discussed above, transfer of the induced gC antibodies alone was not sufficient for solid protection, and, therefore, the presence of immune T cells seems to be required for full protective capacity of immune serum antibodies, as also reported for herpes simplex virus type 2 (HSV-2) infection (36).…”
Section: Discussionmentioning
confidence: 81%
“…The capacity to protect the nervous system is most noteworthy as a desirable characteristic of vaccine-mediated protection against sexually transmitted herpesviral disease, and we observed nearly complete protection of the CNS from acute infection after genital challenge of immunized mice. We were unable to accurately assess latent genome loads in dorsal root ganglia, but genome loads of challenge virus in immunized immunodeficient mice are very low (24) and may be even lower in the fully immunocompetent mice used in this study.…”
Section: Discussionmentioning
confidence: 93%
“…The greatest impact on the replication of HSV-2 in the vaginal mucosa, particularly over the first 2 days postchallenge, was observed in mice receiving the high immunizing dose of 5B86. Previous work with replication-defective HSV-2 indicated that immune antibody and CD4 T cells work synergistically to protect the genital tract from HSV-2 replication during this period but are not independently effective (21,24). Thus, improved CD4 Tcell responses in 5B86-immunized mice may assist antibody to better control early replication of challenge virus in the vaginal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В интерфероновом и цитокиновом статусе при рецидивирующей герпетической инфекции реги-стрируют снижение продукции стимулированного ИФН-γ, что свидетельствует об истощении меха-низмов противовирусной защиты, и тенденцию к гиперпродукции ИЛ-4, свидетельствующую о нали-чии Th 2 -иммунного ответа, который при ГВИ явля-ется неполноценным [25]. Гиперпродукция стиму-лированного ИФН-γ при атипичной герпетической инфекции может быть следствием незначительной, но постоянной антигенной стимуляции [26].…”
Section: патогенез (иммунологические аспекты)unclassified